Antagonist of cIAP1/2 and XIAP enhances anti-tumor immunity when combined with radiation and PD-1 blockade in a syngeneic model of head and neck cancer. (2nd September 2018) - Xiao, Roy; Allen, Clint T.; Tran, Linda; Patel, Priya; Park, So-Jin; Chen, Zhong; Van Waes, Carter; Schmitt, Nicole C.
ABSTRACT: Head and neck squamous cell carcinomas (HNSCCs) frequently harbor genomic mutations in cell death pathways. Nearly 30% of HNSCCs overexpress Fas-Associated Death Domain (FADD), with or without BIRC2/3 genes encoding cellular Inhibitor of Apoptosis Proteins 1/2 (cIAP1/2), critical components of the Tumor Necrosis Factor (TNF) Receptor signaling pathways. ASTX660 is a novel non-peptidomimetic antagonist of cIAP1/2 and XIAP under evaluation in a clinical trial for advanced solid tumors and lymphomas. Herein, we show that ASTX660, at nanomolar concentrations, sensitized Murine Oral Cancer (MOC1) cells to TNFα. Using syngeneic mouse models, ASTX660 showed additive anti-tumor activity with radiation therapy (XRT), cisplatin chemotherapy, and PD-1 blockade to significantly delay or eradicate MOC1 tumors. These combinations significantly increased CD8 + T cells and dendritic cells, as well as T cell activity. ASTX660 stimulated cytotoxic T lymphocyte (CTL) killing of MOC1 cells expressing ovalbumin. Early stages of CTL killing were predominantly mediated by perforin/granzyme B, whereas later stages were mediated by death ligands TNFα, TRAIL, and FasL. Correspondingly, depletion of CD8 + T cells and NK cells in vivo revealed both types of immune cells to be important components of the complete anti-tumor response enhanced by ASTX660+XRT. These findings serve to inform future studies of IAP inhibitors and support the potential for future clinical trials investigating ASTX660 with XRT and immunotherapies like PD-1/PD-L1 blockade in HNSCC.